PERISTILAHAN ASING DALAM HARIAN RIAU POS PEKANBARU - nfn Marnetti (Madah: Jurnal Bahasa dan Sastra, 2016)
This article aims at describing kinds of foreign language terms and their usage in headline news in Riau Pos newspaper for the period of July to August 2015 by applying descriptive method. Data that have been collected then analyzed by the theory of forming terms so that the foreign terms in the headline news can be observed. After analyzing the data, they were classified based on the process of creating equivalent terms. The result of the study shows that the kinds of term by the process of creating equivalent terms, among others 1) direct translation, and translation by inventing new terms. The foreign language terms are written in italic. The source language is English. Some of the foreign terms are completed with the meaning in bahasa Indonesia. Besides, some others have the same forms in bahasa Indonesia and the others are absorbed from the foreign language with the adjustment of written forms in bahasa Indonesia.